Dimethyl malonate alleviates obstructive nephropathy by enhancing renal metabolism and inhibiting kidney oxidative stress and inflammation - Zhang, Wei; Fu, Changde; Lai, Jinjin; Xin, Jun; Zhang, Wenbin (Frontiers in Pharmacology, 2025)
IntroductionObstructive nephropathy is a leading cause of renal injury and fibrosis. Mitochondrial dysfunction represents a hallmark of obstructive nephropathy, a condition that leads to metabolic aberrations, succinate accumulation, reactive oxygen species (ROS) overproduction, tubular damage, and kidney inflammation. Succinate dehydrogenase (SDH) is central to mitochondrial metabolism and targeting SDH with dimethyl malonate (DMM) has been shown to be effective in treating renal ischemia-reperfusion (IR) injury in the murine model. However, the therapeutic potential and underlying mechanisms of DMM against obstructive nephropathy have not been investigated.MethodsWe utilized the unilateral ureteral obstruction (UUO) mouse model to investigate the therapeutic potential of DMM in obstructive nephropathy. Histology, renal fibrosis, and inflammation were analyzed. A murine tubular cell line was used to investigate molecular mechanisms.ResultsDMM administration mitigated UUO-induced renal fibrosis. Transcriptome analysis revealed that DMM promoted mitochondrial function and inhibited renal inflammation in UUO kidneys. The upregulated genes in DMM-treated mice were enriched in metabolic pathways related to fatty acids, organic acids, amino acids, and the PPAR signaling. DMM suppressed the accumulation of CD4+ T cells and the production of inflammatory cytokines in UUO kidneys. Moreover, DMM reduced oxidative stress by decreasing mitochondrial ROS production in tubular cells. Mechanistically, at least in part, DMM activated the PPAR signaling pathway in tubular cells, thereby enhancing fatty acid oxidation (FAO) activity and mitochondrial function. Pharmacological activation of PPAR protected against UUO-induced kidney fibrosis and inflammation.ConclusionOur study suggests that targeting SDH with DMM could be a promising therapeutic strategy for obstructive nephropathy.